Impact of Global and Chinese Cultural Values on Young People's Perceptions of Parenthood in Hong Kong, China. - Ng Yin-ling, Tabitha (Pertanika Journal of Social Sciences & Humanities, 2015)
Over the past several decades, fertility has declined almost everywhere in the world. In Hong Kong, young people's perceptions of parenthood seem to be changing rapidly in the pale of a competitive global economy. This paper addresses the views of young Chinese people in relation to parenthood in a society where East meets West. The study is a qualitative research with a cross-sectional design and a focus group approach. The aim is to explore the possible impact of global and Chinese cultural values on young people's perceptions of parenthood. Data was collected in six audiotaped focus group interviews with 40 young people aged 17 to 25. A mix of purposive and snowball sampling was used. The findings suggest that traditional cultural values such as family security and relationships, honouring of parents and elders and family loyalty are still strongly supported by many young adults. However, the sample youth was also influenced by global values such as freedom, personal goals, ambition, wealth, pleasure and a varied life. Many young people prefer to have children for reasons which seem to be linked to global values of individualism, liberalism and intrinsic rewards. Reasons of having children are less about continuing the family line but more as a means to maintain the marriage. There is also a trend of delayed parenthood. Some young people do not consider having children due to such reasons as personal development and structural factors as prolonged continuing education, long working hours, cross-border work and low salary. The insights from this study inform service providers, policy makers and interested parties who together can jointly map out appropriate youth and family interventions to assist young people in their transition to young adulthood.